2019
DOI: 10.1155/2019/2594149
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates for Secondary Prevention of Osteoporotic Fractures: A Bayesian Network Meta-Analysis of Randomized Controlled Trials

Abstract: Purpose To investigate the comparative efficacies of the five most commonly used bisphosphonates for the secondary prevention of osteoporotic fractures in a Bayesian network meta-analysis. Methods Five databases and the reference lists of all acquired articles from inception to July 2017 were searched. A Bayesian random-effects model was employed, and vertebral, hip and nonvertebral nonhip fractures were assessed by odds ratios (ORs) and 95%credible intervals. Furthermore, with respect to each endpoint, rank p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…The administration of BPs as anti-osteoporotic drugs has been confirmed to effectively prevent bone loss and increase bone quality and density. Several studies have verified that BPs decrease the risk of vertebral and non-vertebral fractures (5,24). The present meta-analysis revealed that zoledronic acid not only significantly improved post-operative BMD at 6 and 12 months but also decreased the incidence of additional vertebral body fractures.…”
Section: Discussionsupporting
confidence: 59%
“…The administration of BPs as anti-osteoporotic drugs has been confirmed to effectively prevent bone loss and increase bone quality and density. Several studies have verified that BPs decrease the risk of vertebral and non-vertebral fractures (5,24). The present meta-analysis revealed that zoledronic acid not only significantly improved post-operative BMD at 6 and 12 months but also decreased the incidence of additional vertebral body fractures.…”
Section: Discussionsupporting
confidence: 59%
“…[37] studying IV zoledronic acid versus oral risedronate in the prevention and treatment of glucocorticoid‐induced osteoporosis, zoledronic acid was reported to be more efficacious than risedronate in increasing the lumbar spine BMD at 12 months. A recent network meta‐analysis concluded that oral alendronate was the most efficacious among five commonly used bisphosphonates (alendronate, risedronate, ibandronate, zoledronate, and etidronate) in preventing vertebral and hip fractures, while zoledronic acid was most efficacious in preventing nonvertebral nonhip fractures [38].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been some meta-analyses and systematic reviews that included the effects of bisphosphonates on the IHF. In these meta-analyses and systematic reviews, bisphosphonates significantly reduced the IHF; however, none of them reported results stratified according to patient age or the kind of bisphosphonate used 1–3 30…”
Section: Introductionmentioning
confidence: 99%